Embodied research methods - Thanem, Torkild; Knights, David, 1940- (London : SAGE Publications, Ltd, 2019)
Disembodied research erects false dichotomies between flesh and reason, and between the corporeal and the social. By contrast, Torkild Thanem and David Knights engage with approaches and practices that exploit the body's capacity to generate knowledge, craft lively accounts, and create fleshy concepts. These approaches enrich our understanding of how people live, work, and interact with their bodies within the social world. Thanem and Knights discuss methods, practices, and personal experiences which involve bodies in the research process -- in generating and analysing empirical material, reflecting on the work they do as researchers, and turning research into written text. Embodied Research Methods is an important and practical resource for undergraduate and postgraduate students across the social sciences, and a thought-provoking read for researchers in these areas.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social sciences -- Research -- Methodology